Blow up of Coupled Nonlinear Klein-Gordon System with Distributed Delay, Strong Damping, and Source Terms - Djamel Ouchenane; Salah Mahmoud Boulaaras; Asma Alharbi; Bahri Cherif (Journal of Function Spaces)
This present work deals with the blow up of the coupled Klein-Gordon system with strong damping, distributed delay, and source terms, under suitable conditions.